Sclerocarya Birrea (Anacardiaceae) Stem-Bark Extract Stimulates Protein Kinase Akt And AMPK Pathways in The Liver in a Diet-Induced Obesity Mouse Model. - ATTAKPA, S. EUGÈNE; SEZAN, ALPHONSE; BABA-MOUSSA, LAMINE; Seri, Bialli; Gbéassor, Messanvi; Khan, Naim Akhtar (My University, 2015)
Background: The present study was undertaken to evaluate the anti-diabetic of sclerocarya birrea (A. Rich) Hochst in a diet-induced obesity (DIO) mouse model. Obesity-induced contributes to the development of obesity-related metabolic disorders such as insulin resistance, type 2 diabetes, fatty liver disease, and cardiovascular disease. In this study, we investigated whether sclerocarya birrea can reduce obesity-induced and metabolic disorders such as insulin resistance and hepatic steatosis. Methods: Male C57BL/6 obese mice fed a high-fat diet for 10 weeks were administered orally by gastric intubation sclerocarya birrea extract at a dose of 200 or 300 mg/kg body weight, for a further 10 weeks and were compared with HFD-control group. Diets were prepared freshly every week and stored at 4oC. The food and the water were provided ad libitum and replenished every 3-4 days. During the study, serum glucose level was measured at the same time in the morning. Serum insulin was determined using an ELISA kit, according to the manufacturer’s instructions. Serum glucose was determined by the glucose oxidase method using a glucose analyser. After liver lipid extraction according to the method of Folch et al., liver TG content was measured by using a commercially available kit. Free fatty acids (FFA) were separated on silica gel by thin layer chromatography (TLC). The purified fractions of FFA and TG were quantified by gas liquid chromatography. As well as liver and kidney functional parameters (ALT, AST, creatinine, alkaline phosphatase) were assessed. The expression of the liver protein was analyzed by Western blot. Results: At the end of the study, insulin sensitive tissue (liver) collected to investigate anti-diabetic effects and examine the plant’s molecular mechanisms. sclerocarya birrea also reduced Serum glucose. Noteworthy, 200 mg/kg sclerocarya birrea efficiently reduced glycaemia although plasma insulin levels were similar to diabetic controls while preventing hepatic steatosis (Sclerocarya birrea diminished hepatic triglyceride, free fatty acids) in DIO mice. Western immunoblot analysis, demonstrated that sclerocarya birrea stimulated two pathways: the insulin dependent Akt and the insulin independent AMPK ones. The improvement of hepatic steatosis observed in DIO treated mice was associated with a decrease in the hepatic content of SREBP-1, a transcription factor involved in de novo lipogenesis. Sclerocarya birrea treatment had tendency to increase hepatic PPARα levels beyond those of control DIO animals. Sclerocarya birrea treatment did not alter liver (ALT, AST) or renal (creatinine and alkaline phosphatase) functional parameters in the blood, thereby attesting to the lack of toxicity of the plant extract in diet-induced obesity mice. Conclusion: These data suggest that sclerocarya birrea exerts potential anti-diabetic action by improving insulin sensitivity and mitigating high-fat diet-induced obesity and hyperglycemia. They also validate the safety and efficacy of this plant.
Keywords: Mouse; sclerocarya birrea; type 2 diabetes mellitus; insulin resistance; DIO mice; hyperglycemia; hyperinsulinemia; AKT; AMPK; SREBP-1; PPARα.